2015
DOI: 10.1208/s12249-015-0378-x
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Mentha Oil in Chitosan Polymer Matrix Alleviates Skin Irritation

Abstract: Abstract. Mentha spicata L. var. viridis oil (MVO) is a potent antifungal agent, but its application in the topical treatment is limited due to its irritancy and volatility. It was aimed to develop more efficient, chitosan-incrusted MVO microspheres with reduced volatility and lesser irritancy and to dispense it in the form of ointment. Simple coacervation technique was employed to microencapsulate MVO in chitosan matrix. Morphological properties and polymer cross-linking were characterized by scanning electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In spite of the fact that thymol is a GRAS approved food additive, some researches indicated that thymol could cause irritation of mouth tissues because of its membrane affinity and hydrophobicity1920. It has been reported recently that micelle encapsulation could alleviate irritation of bioactive compounds, such as capsaicin21 and menthe oil22. Although the side effects of thymol might be alleviated by encapsulation, the safety should be still thoroughly assessed before the practical applications in food systems.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of the fact that thymol is a GRAS approved food additive, some researches indicated that thymol could cause irritation of mouth tissues because of its membrane affinity and hydrophobicity1920. It has been reported recently that micelle encapsulation could alleviate irritation of bioactive compounds, such as capsaicin21 and menthe oil22. Although the side effects of thymol might be alleviated by encapsulation, the safety should be still thoroughly assessed before the practical applications in food systems.…”
Section: Resultsmentioning
confidence: 99%
“…The collected samples were analyzed by UV spectrophotometer (Perkin Elmer, Waltham, MA, USA) at 223 nm after appropriate dilution. The experiment was performed in triplicate [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Microencapsulated oils have a wide variety of applications across a range of industries, including food, household, 1 cosmetic, 2 and pharmaceutical 3 products. Encapsulation within a polymeric shell not only allows their dispersal in a polar environment but also offers benefits such as protection from oxygen degradation, 4 improved retention of volatile components, 1 and controlled release of the contents.…”
Section: Introductionmentioning
confidence: 99%
“…Encapsulation within a polymeric shell not only allows their dispersal in a polar environment but also offers benefits such as protection from oxygen degradation, 4 improved retention of volatile components, 1 and controlled release of the contents. 3 The diameter of microcapsules can range between 1 μm and a few mm, 5 making them small enough to pass through wastewater treatment plants into aquatic environments, 6 contributing to microplastic pollution when synthetic and non-biodegradable wall materials are used (e.g., polyethylene glycol, 7 polymethyl methacrylate, 8 or melamine-formaldehyde 1 ). The environment is polluted with 36,000 tons of microplastics each year in the EU alone 9 and concerns over the implications for aquatic life and human health have grown with the emergence of studies confirming the presence of microplastics in the entire human food supply chain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation